THE ROLE OF ELECTRONIC WORD OF MOUTH IN MEDIATING THE EFFECT OF DIGITAL MARKETING ON PROPERTY PURCHASE DECISIONS - Usman Usman; Hafni Sandi; Handris; Zabir Zainuddin; Wa Ode May Zhara Averina (Journal Economics Technology And Entrepreneur, 2026)
This study examines the effect of digital marketing on property purchase decisions through the mediating role of electronic word of mouth (e-WOM) among consumers of Margahayu Housing, Kendari. A quantitative explanatory approach was employed using a survey of 172 consumers selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using SEM-PLS with SmartPLS 4. The findings reveal that digital marketing has a positive and significant effect on e-WOM and directly influences purchase decisions. Furthermore, e-WOM significantly affects purchase decisions and partially mediates the relationship between digital marketing and purchase decisions. These findings indicate that effective digital marketing strategies encourage positive online consumer communication, which strengthens consumers' confidence in making property purchase decisions. This study contributes to the digital marketing literature by highlighting the strategic role of e-WOM in the property sector.